Analisis Performansi Sistem Produksi Genteng (Studi Kasus: PT. XYZ , Cikokol) - Trifenaus Prabu Hidayat; Indra Kusno (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2013)
This research discusses the proposed implementation of lean manufacturing system at PT. MONIER. PT.MONIER is a manufacturing company engaged in the production of tiles with 3 types of product that is Exeltile, Centurion tile and Elabana tile. PT. MONIER is using push system as their production system methodat the moment. Current state value stream mapping is made to see shop floor as a big picture. Calculationshows that current state Process Cycle Efficiency (PCE) is very low with only 4,51%. The company still farfrom “lean” because minimum requirement of a company called lean when the value of PCE more than30%. Meanwhile, current state Overall Equipment Effectiveness (OEE) is 79,98%. From the observation, itcan be found that there are many non-value added activity (waste) at PT. MONIER factory. From theidentification of waste using check sheet and cost calculation resulted by wastes, it was found that inventorywaste post the biggest cost with 92,8% of the total cost of existing waste. With further analyze, it is knownthat the root cause from inventory waste is due to the company allow overproduction and there is wrongphilosophy against inventory. Those root causes which has found before is to be eliminated with leanmanufacturing system approach. There are several methods that will be applied in PT. MONIER such as 5Simplementation and standarized work, then future state value stream mapping is made to see all proposedmethods in a big picture. In addition, this future state condition will be simulated to give a betterperspective. With the implementation of lean manufacturing system, future condition is as same as currentstate value condition. Future state Process Cycle Efficiency (PCE) is 4,51% and future state OverallEquipment Effectiveness (OEE) is 79,98%. This happens because the theory and methods of lean from leanmanufacturing system can only be applied on the assembly line and one piece flow.